In vitro effects of mycophenolic acid and allopurinol against Leishmania tropica in human macrophages. - Berman, J D (1982)
The possibility that purine inhibitors or analogs might be effective antileishmanial agents led to the determination of the antileishmanial activity of mycophenolic acid and allopurinol in vitro. The drugs were tested against Leishmania tropica amastigotes (mammalian forms) within human macrophages, a model in which achievable serum concentrations of antileishmanial agents currently in use eliminate approximately 90% of the parasites. Mycophenolic acid, an inhibitor of guanosine nucleotide synthesis from inosinic acid, was shown here to inhibit guanosine nucleotide synthesis in L. tropica promastigotes (insect forms). When tested against L. tropica amastigotes within macrophages, mycophenolic acid eliminated 50% of the parasites at achievable peak human serum levels (20 micrograms/ml) and 40% of the parasites at trough serum levels (1 to 10 micrograms/ml). This demonstrates that an inhibitor of guanosine nucleotide synthesis is partially effective against L. tropica in vitro. The purine analog allopurinol was also tested and was found to eliminate 50% of L. tropica amastigotes in this model. Because mycophenolic acid and allopurinol are partially, but not completely, effective antileishmanial agents in this in vitro model, their in vivo utility remains to be determined by clinical trials.